AC-driven multicolor electroluminescence from a hybrid WSe2 monolayer/AlGaInP quantum well light-emitting device. Issue 3 (23rd December 2022) - Chang, Ya-Hui; Lin, Yen-Shou; James Singh, Konthoujam; Lin, Hsiang-Ting; Chang, Chiao-Yun; Chen, Zheng-Zhe; Zhang, Yu-Wei; Lin, Shih-Yen; Kuo, Hao-Chung; Shih, Min-Hsiung
Abstract : A multicolor AC-driven light-emitting device by integrating a WSe2 monolayer and AlGaInP–GaInP multiple quantum well (MQW) structures. Abstract : Light-emitting diodes (LEDs) are used widely, but when operated at a low-voltage direct current (DC), they consume unnecessary power because a converter must be used to convert it to an alternating current (AC). DC flow across devices also causes charge accumulation at a high current density, leading to lowered LED reliability. In contrast, gallium-nitride-based LEDs can be operated without an AC–DC converter being required, potentially leading to greater energy efficiency and reliability. In this study, we developed a multicolor AC-driven light-emitting device by integrating a WSe2 monolayer and AlGaInP–GaInP multiple quantum well (MQW) structures. The CVD-grown WSe2 monolayer was placed on the top of an AlGaInP-based light-emitting diode (LED) wafer to create a two-dimensional/three-dimensional heterostructure. The interfaces of these hybrid devices are characterized and verified through transmission electron microscopy and energy-dispersive X-ray spectroscopy techniques. More than 20% energy conversion from the AlGaInP MQWs to the WSe2 monolayer was observed to boost the WSe2 monolayer emissions. The voltage dependence of the electroluminescence intensity was characterized. Electroluminescence intensity–voltage characteristic curves indicated that thermionic emission was the mechanism underlying carrier injection across the potential barrier at the Ag–WSe2 monolayer interface at low voltage, whereas Fowler–Nordheim emission was the mechanism at voltages higher than approximately 8.0 V. These multi-color hybrid light-emitting devices both expand the wavelength range of 2-D TMDC-based light emitters and support their implementation in applications such as chip-scale optoelectronic integrated systems, broad-band LEDs, and quantum display systems.